2016
DOI: 10.3390/met6110286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Thermodynamic Behavior of Selective Laser Melting on the Formation of In situ Oxide Dispersion-Strengthened Aluminum-Based Composites

Abstract: This paper presents a comprehensive investigation of the phase and microstructure, the thermodynamic behavior within the molten pool, and the growth mechanism of in situ oxide dispersion-strengthened (ODS) aluminum-based composites processed by a selective laser melting (SLM) additive manufacturing/3D printing process. The phase and microstructure were characterized by X-ray diffraction (XRD) and a scanning electronic microscope (SEM) equipped with EDX, respectively. The thermodynamic behavior within the molte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Extremely high cooling rates inherent in SLM allow this phenomenon to be successfully avoided and allow a uniform distribution of reinforced particles to be obtained, as it was accomplished on the powder mixing/milling stage. Jue et al [ 63 , 80 ] also considered the distribution of alumina in the Al matrix specifically for SLM, taking into account the Marangoni convection and induced liquid capillary forces that accelerate the particle rearrangement, making it possible to obtain a homogeneous structure after SLM. Han et al [ 84 ] studied the melting pool temperature during SLM with a 200 W laser power.…”
Section: Melting Pool Behaviormentioning
confidence: 99%
“…Extremely high cooling rates inherent in SLM allow this phenomenon to be successfully avoided and allow a uniform distribution of reinforced particles to be obtained, as it was accomplished on the powder mixing/milling stage. Jue et al [ 63 , 80 ] also considered the distribution of alumina in the Al matrix specifically for SLM, taking into account the Marangoni convection and induced liquid capillary forces that accelerate the particle rearrangement, making it possible to obtain a homogeneous structure after SLM. Han et al [ 84 ] studied the melting pool temperature during SLM with a 200 W laser power.…”
Section: Melting Pool Behaviormentioning
confidence: 99%
“…Rosenthal et al [28], also reported a decline in the ductility that is inversely proportional to the strain rate, which suggests the effects of confined strain rate hardening had not taken place, and that the existence of the silicon phase could be predominantly the reason for this conduct. Brandao et al [29] used stress relief to prevent the residual stress from distorting the components. The effect was the same as in this work, as it led to a drastic decrease in the static yield strength.…”
Section: Tensile Strength After Stress Relievingmentioning
confidence: 99%
“…In the recent years, the in situ approach for AM gained much attention among researches. [ 11ā€“25 ] For instance, Promakhov et al [ 24 ] produced Inconel 625/TiB 2 MMC material applying selfā€propagating highā€temperature synthesis (SHS). Obtained blocks were grinded to a coarse powder and then plasma spheroidized yielding spherical particles with TiB 2 reinforcements of 0.5ā€“5 Ī¼m size.…”
Section: Introductionmentioning
confidence: 99%